Mixed Group 14–15 Metalates as Model Compounds for Doped Lead Halide Perovskites. Issue 8 (15th January 2021) - Dehnhardt, Natalie; Luy, Jan‐Niclas; Klement, Philip; Schipplick, Luca; Chatterjee, Sangam; Tonner, Ralf; Heine, Johanna
Abstract: Doping and alloying are valuable tools for modifying and enhancing the properties and performance of lead halide perovskites. However, the effects of heterovalent doping with Sb 3+ and Bi 3+ cations are still a matter of current investigation. Due to the different charge of the dopants compared to the constituting Pb 2+ ions, a simultaneous creation of defects is unavoidable and the influence of these defects and the actual metal substitution become entangled. Herein, we present the first 14–15 iodido metalates, (BED)4 PbE2 I16 (BED=N‐benzylethylenediammonium; E=Sb (1 ), Bi (2 )), which are model compounds for doped lead iodide perovskites and display surprisingly low band gaps of 2.01 (1 ) and 1.88 eV (2 ). Quantum chemical investigations show that this stems from a good electronic match between the PbI6 and EI6 units of the compounds. Our results provide a model system for doped perovskites, but also represent the first examples of a promising new class of metal halide materials. Abstract : The electronic nature of Sb‐ and Bi‐doped lead halide perovskites is an area of current scientific debate. Model compounds featuring [PbE2 I16 ] 8− (E=Sb, Bi) anions that represent precise cut‐outs of doped perovskites are presented. The compounds display surprisingly low band gaps owing to an excellent electronic match between PbI6 and EI6 units and represent the first members of a promising new class of metal halide materials.